IMPLEMENTATION OF WEB-BASED APPLICATIONS ONLINE SINGLE SUBMISSION RISK BASED APPROACH (OSS-RBA) IN PUBLIC SERVICES AT THE SUB-DISTRICT OFFICE OF SUNGAI AMBAWANG KUBU RAYA DISTRICT - Ade Risna Sari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The focus of this research is on the Implementation of Web-Based Applications Online Single Submission Risk Based Approach (OSS-RBA) in Public Services at the Sungai Ambawang District Office, Kubu Raya Regency. In the implementation of the Online Single Submission Risk Based Approach (OSS-RBA) web -based application in public services at the Sungai Ambawang District Office, Kubu Raya Regency, there are obstacles. These obstacles include the variable characteristics of the implementing agent, where initially the business actors refused to process business licences online or through the Online Single Submission Risk Based Approach (OSS- RBA) application . Another obstacle is the variable of facilities and infrastructure resources, where computer office equipment is outdated and the internetnetwork is sometimes not smooth so that the Online Single Submission Risk Based Approach (OSS-RBA) web-based application cannot be accessed quickly. The purpose of this study was to describe and analyse how the implementation process of the Online Single Submission Risk Based Approach (OSS-RBA) web-based application in public services at the Sungai Ambawang District Office, Kubu Raya Regency. As an analytical knife to examine this research, the author uses the theory of Donald S. Van Meter and Carl E. Van Horn, which explains that there are five variables that affect implementation performance, namely 1) standards and objectives; 2) resources; 3) inter-organisational communication and strengthening activities; 4) characteristics of implementing agents; and 5) social, economic and political conditions. This paper is analysed using a descriptive method through a qualitative approach. Research results were obtained through field observations and interviews with key informants and supporting informants as well as using documentation techniques. The target output of this research is to contribute suggestions to the Sungai Ambawang District Office of Kubu Raya Regency so that the implementation of the Online Single Submission Risk Based Approach (OSS-RBA) web-based application in public services at the Sungai Ambawang District Office of Kubu Raya Regency can be effective and efficient.